Improving Teachers 'Abilities In Video Based Learning By Using Microsoft Powerpoint Application Through Workshop - Movitaria, Mega Adyna; Shandra, Yosi (Universitas Pahlawan Tuanku Tambusai, 2020)
This research was conducted based on the fact that the low ability of teachers in making learning media had an effect on school quality. The purpose of this study was to determine the increase in the ability of teachers to make instructional videos based on the Microsoft PowerPoint application on Teacher Elementary school workshops. This research is a descriptive quantitative research with a population of 25 people. The data collection technique in this study uses a questionnaire method. The results showed that the workshop for making instructional media could improve the ability of teachers to create and use video learning media based on the Microsoft PowerPoint application. Researchers suggest that Microsoft PowerPoint can be used by teachers in making instructional videos.